Phylogenetic affinities of evolutionarily enigmatic African galliforms: the Stone Partridge Ptilopachus petrosus and Nahan’s Francolin Francolinus nahani, and support for their sister relationship with New World quails - Cohen, Callan; Wakeling, Julia L.; Mandiwana-Neudani, Tshifhiwa G.; Sande, Eric; Dranzoa, Christine; Crowe, Timothy M.; Bowie, Rauri C. K. (Ibis, 2012)
The monotypic Stone Partridge Ptilopachus petrosus (Galliformes: Phasianidae), restricted to arid rocky areas of the northern savanna belt including the Sahel on the southern border of the Sahara Desert, is a taxonomic enigma. Historically, it has been grouped with Asian forest partridges (Galloperdix and Bambusicola spp.). However, recent DNA-based phylogenetic research has suggested that its closest relative is Nahan’s Francolin Francolinus nahani, another taxonomically enigmatic African galliform, and a globally threatened, narrow endemic species associated with the interior of remnant primary forests of the eastern equatorial lowlands of the Democratic Republic of the Congo and Uganda. This hypothesis is investigated in greater detail using additional DNA evidence and information on behaviour and vocalizations. Phylogenetic analyses of the combined sequences from three nuclear and four mitochondrial markers (5554 bases for 84 galliform taxa) overwhelmingly support the sister relationship between F. nahani and P. petrosus. They, in turn, are the distantly related sister taxon of the New World quails (Odontophoridae), and are not related to any other Old World galliform.
Keywords: Biogeography; Odontophoridae; Phasianidae; Taxonomy